Long-term exposure of rabbits to imidaclorpid as quantified in blood induces genotoxic effect. (April 2016) - Stivaktakis, Polychronis D.; Kavvalakis, Matthaios P.; Tzatzarakis, Manolis N.; Alegakis, Athanasios K.; Panagiotakis, Michael N.; Fragkiadaki, Persefoni; Vakonaki, Elena; Ozcagli, Eren; Hayes, Wallace A.; Rakitskii, Valerii N.; Tsatsakis, Aristidis M.
Abstract: The present in - vivo study focuses on the genotoxic effect of the neonicotinoid pesticide imidacloprid (IMI) in rabbits. The purpose of the study was to establish a possible relationship between exposure to the pesticide (dose and duration) and genotoxicity. Furthermore, an analytical method for the simultaneous determination of IMI and its major metabolite 6-chloronicotinic acid (6-ClNA) in blood was developed and validated. The isolation of the two analytes from blood was performed by liquid–liquid extraction with dichloromethane. Analysis was performed by Liquid Chromatography – Atmospheric Pressure Chemical Ionization – Mass Spectrometry (LC-APCI-MS). The method was applied on the determination of IMI and 6-ClNA in serum samples obtained from rabbits fed with the insecticide at two low doses. Furthermore, parameters of genotoxicity and cytotoxicity were evaluated by measuring binucleated cells with micronuclei (BNMN), micronuclei (MN) and the Cytokinesis Block Proliferation Index (CBPI), in lymphocytes of exposed rabbits. The results revealed a genotoxic effect of IMI for both exposed groups. There were statistically significant differences in the frequencies of BNMN and MN between control and exposed groups but there was no dose-dependence, neither time-dependence of the genotoxic effect for the administered doses. This is the first time that long term exposure to IMI in rabbits was studied for the determination of its genotoxic effect. The genotoxic effect of IMI as it is depicted by the current study is in accordance with previous studies. Graphical abstract: Highlights: An LC-APCI-MS method for the detection of imidacloprid in blood of exposed rabbits was developed. Imidacloprid levels in blood of exposed rabbits were dose dependent. Imidacloprid induced significant increase of micronuclei in rabbits. The Cytokinesis Block Proliferation Index indicated a lack of cytotoxicity.